Evaluation of the Relationship Between Cooking and Food Preparation Skills and Dietary Intake, Body Mass Index, and Body Composition in University Students. - BOYOğLU, Sena Nur; TOKPUNAR, Merve (Nutrición Clínica y Dietética Hospitalaria, 2024)
Having cooking and food preparation skills can improve the nutritional and dietary quality of individuals. This study aimed to evaluate the relationship between cooking and food preparation skills and food consumption, body mass index and body composition in university students. The study was conducted on 242 individuals aged 18 years and over who were studying at Biruni University between March and May 2023. Demographic characteristics, anthropometric measurements, dietary habits, knowledge about cooking and food preparation, frequency of food consumption according to cooking methods, cooking and food preparation skills and 24-hour food consumption were questioned by applying a data collection form with face-to-face interview and measurement analysis with Bioelectrical Impedance Analysis device. The Cooking and Food Preparation Skills (CS and FPS) scale developed by Lavelle et al. was used to question skills. The relationship between cooking and food preparation skills, food consumption and anthropometric measurements was investigated by correlation test. There was a significant negative correlation between the total cooking and food preparation skills scale score and carbohydrate consumption in women and a significant positive correlation between energy, protein, fat, magnesium and vitamin D consumption in men (p<0.05). Although there was a positive correlation between total scale score and BMI in women and men, no significance was found (p>0.05). Although there was no significant relationship between total scale score and anthropometric measurements in females, there was a significant positive relationship between total scale score and muscle mass in males (p<0.05). In conclusion, improving cooking and food preparation skills may be an important strategic element to support university students to achieve healthy eating and body composition goals.